Utricularia sunilii (Lentibulariaceae), a striking new species from southern Western Ghats, Kerala, India - Kumar, Vannaratta Veettil Naveen; Prabhukumar, Konickal Mambetta; Jagadeesan, Raveendran; Harinarayanan, Cheruppoyilath Mana; Nair, Maya C.; Janarthanam, Malapati K.; Balachandran, Indira (Phytotaxa, 2018)
Utricularia sunilii, a new species of Utricularia Sect. Oligocista from Kerala state of Western Ghats is described here. The new species shows similarities with U. graminifolia in having 3-nerved foliar organs and thickened capsule wall along the margin of dehiscence but differs by deeply 3-lobed lower lip of corolla.